Mutual fund performance and the validity of fund manager's outperformance claims in G7 economies: an empirical investigation - Darniya, Prabu (2024)
Mutual funds are prominent in the global capital market, offering diversification and professional management to individual investors. In view of their crucial role in the global financial landscape, this study aims to assess mutual funds' ability to outperform market benchmarks, evaluate fund managers' stock selection skills, and investigate market timing across G7 countries The dataset includes 50 mutual funds (25 equity-based and 25 bond-based) from each G7 nation between 2015 and 2022. Various performance metrics such as Sharpe Ratio, Treynor Ratio, Jensen’s Alpha, and market timing models are employed. Our findings generally support the efficient market hypothesis (EMH), as most G7 mutual funds fail to outperform market benchmarks. Negative Sharpe and Treynor ratios across the sample suggest insufficient risk-adjusted returns. Additionally, the lack of positive Jensen’s Alpha and weak performance under the Fama-French three-factor model indicate that most fund managers lack stock-picking skill. However, a few funds from the US and UK do exhibit positive Jensen’s Alpha, suggesting that skilled management may be present in some cases. In terms of market timing, only Italian fund managers demonstrate statistically significant positive abilities, while fund managers in other countries show limited or negative timing skills. These findings suggest that, contrary to the hopes of active management, most G7 mutual funds do not consistently outperform the market, aligning with the core prediction of EMH. Similarly, actively managed exchange-traded funds (ETFs) show limited success in outperforming passive benchmarks. These findings emphasize the importance of carefully evaluating fund performance before making investment decisions and tempering expectations regarding the potential for abnormal returns from actively managed funds. Investors should consider focusing on low-cost passive investment strategies, particularly in light of the limited evidence for consistent outperformance in active management.